O pronome te em ambientes de resistência : um estudo em funcionalismo clássico - Farias, Amanda Brito de Medeiros (2021)
The environments of resistance are those in which the clitic te is variable, being in the face of linguistic forms that function in the same syntactic context, in the face of the set of verbs with which it occurs, in terms of the semantic type of the verb, in relation to ordering and structure. of the prayer in which he is involved. The semantics of the prototypes reused the notion of trait or component for that of attribute, in order to differentiate from the traditional focus on categorization and meaning. There must be more central (prototypical) characteristics than others if there are more representative individuals. The general objective of this research is to identify the environments of resistance of te as a prototypical clitic for the expression of the 2nd person singular (hereinafter 2SG) in the object function in Brazilian Portuguese from the perspective of classical functional linguistics. We investigated the problem that research dedicated to the complementation of 2SG deals with the alternation of linguistic forms that appear in this position and indicate the regularity of the clitic te in relation to the others. We note that, even in the face of regularity proven in several studies, the te, as a prototype, can find specific environments in which its resistance varies. This problem led to the following questions: “How are the environments of resistance in which te is used?”; “What syntactic-semantic and discursive-pragmatic factors are involved in the resistance of the prototypical clitic te?”; and “How do you quantify te resistance levels in each identified resistance environment?” As a main hypothesis, it is defended that the te, as a prototype, admits punctual environments of variation in its resistance. To verify this hypothesis, data from 2 corpora (C-Oral-Brasil and D&G Natal) were analyzed qualitatively and quantitatively, considering prototypicality as the main theoretical contribution, according to Classical Functional Linguistics. The following preliminary conclusions were possible: In the C-Oral-Brasil data no textual genres were identified, the predominant function is that of indirect object and we relate this to te resistance associated with regularity. About the direct object (OD), we believe it is the environment of resistance where te figures with less strength, but we highlight how this contributes to its establishment as a prototype. As for the “semantic type” environment of the verb in simple verbs and in verbal phrases, we noticed that two types stand out: material/activity verbs and dicendi. In verbal phrases, the two types mentioned present greater balance. From the C-Oral-Brasil data, we observed 4 types of variation in which te appeared in the ordering environment: Auxiliary verb + subject + object + verb (VaSOV); Auxiliary verb + S (deleted) + object + verb (VaSapOV); Auxiliary Verb + Object + Verb (VaOV) and Subject + Auxiliary Verb + Object + Verb (SVaOV). Being more resistant because it is regular, te is more resistant in the SVaOV order. In environments where it needs to resist, being less regular, the VAOV order stands out. Regarding the “pronominal collocation” as an environment of resistance, we do not extend our considerations, as the proclitic collocation is established in the C-Oral-Brasil data.